Osteogenic differentiation of 3D-printed porous tantalum with nano-topographic modification for repairing craniofacial bone defects - Zhang, Chuxi; Zhou, Zhongwei; Liu, Nian; Chen, Jiangping; Wu, Jinyang; Zhang, Yong; Lin, Kaili; Zhang, Shilei (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Congenital or acquired bone defects in the oral and cranio-maxillofacial (OCMF) regions can seriously affect the normal function and facial appearance of patients, and cause great harm to their physical and mental health. To achieve good bone defect repair results, the prosthesis requires good osteogenic ability, appropriate porosity, and precise three-dimensional shape. Tantalum (Ta) has better mechanical properties, osteogenic ability, and microstructure compared to Ti6Al4V, and has become a potential alternative material for bone repair. The bones in the OCMF region have unique shapes, and 3D printing technology is the preferred method for manufacturing personalized prosthesis with complex shapes and structures. The surface characteristics of materials, such as surface morphology, can affect the biological behavior of cells. Among them, nano-topographic surface modification can endow materials with unique surface properties such as wettability and large surface area, enhancing the adhesion of osteoblasts and thereby enhancing their osteogenic ability. Methods: This study used 3D-printed porous tantalum scaffolds, and constructed nano-topographic surface through hydrothermal treatment. Its osteogenic ability was verified through a series of in vitro and in vivo experiments. Results: The porous tantalum modified by nano-topographic surface can promote the proliferation and osteogenic differentiation of BMSCs, and accelerate the formation of new bone in the Angle of the mandible bone defect of rabbits. Discussion: It can be seen that 3D-printed nano-topographic surface modified porous tantalum has broad application prospects in the repair of OCMF bone defects.